Radical Right Islamists in Bangladesh: A Counter-Intuitive Argument. Issue 1 (2nd January 2021) - Ruud, Arild Engelsen; Hasan, Mubashar
Abstract: The radical Right in Europe and Islamist parties in Muslim countries have conventionally been portrayed as fundamentally different. The article uses material from Bangladesh to argue that the two share a wide set of characteristics and can be understood as fundamentally similar. Theoretically, we suggest a concept of the radical Right that encapsulates a set of deeper sentiments found to some extent in any culture or society. These deeper sentiments are normally obfuscated by attention-grabbing current events, but, isolated analytically, can be seen to give rise to parallel developments in different contexts. Our argument expands the theoretical value of the concept of the radical Right and helps understand recent political developments in Muslim-majority Bangladesh and, potentially, the wider authoritarian turn.